Gender attitudes on politics and leadership: A framing experiment - Ma, Ning; Ragasa, Catherine; Kyle, Jordan (International Food Policy Research Institute, 2023)
This paper measures the extent of attitudes toward gender inequality in leadership at different levels of decisionmaking. We also estimated the effect of a subtle gender frame on those gender attitudes through a randomized survey experiment. Using a sample of 241 experts involved in federal- and state-level agri-food policy process in Nigeria, we presented six statements that support gender (in)equality in leadership at different levels and asked the experts to rate each statement using a four-point Likert scale. Study results show persistent gender norms around women’s leadership roles, even among elites and experts: 4–20% of female experts and 30–46% of male experts in our sample still believe that men are better in leadership positions at different levels. Female experts’ gender attitudes did not vary by the level of decision-making and by gender frame; however, males’ gender attitudes varied significantly by the level of decision-making and by the gender frame. Those randomly assigned the gender equality frame (e.g., Women make equally good or better political leaders than men do) were less likely to have attitudes in support of gender inequality in leadership than those randomly assigned the gender-inequality frame (e.g., Men make better political leaders than women do). Male respondents tended to disagree less on the statements that support gender equality than to agree on the statements that support gender inequality. Assessing attitudes through surveys is often challenging and biased, as we show that responses to sensitive gender questions are malleable and sensitive to subtle framing. We demonstrate that subtle frames affect survey responses, which warrants attention to a more careful survey design